A Review of Cryptotanshinone and its Nanoformulation in Cancer Therapy - Liu, Xin; Gao, Yahan; Yang, Fan; Qian, Min; You, Shuhui; Wang, Xiaoxiao; Qin, Fenju; Xiang, Min; Guo, Weiqiang (Anti-Cancer Agents in Medicinal Chemistry, 2025)
Cancer, with a high incidence and mortality rate, has emerged as a major public health problem worldwide. Currently, new approaches, such as targeted therapy and immunotherapy, are giving hope to patients. However, drug resistance and adverse side effects are major barriers to cancer treatment. As a result, there is a greater focus on the development of cancer therapy strategies and medications with low toxicity and high efficacy. Cryptotanshinone (CTS), a diterpenoid quinone extracted from Salvia miltiorrhiza Bunge, exhibits a wide range of biological activities, including immunomodulatory, anti-inflammatory, and antitumor effects. In recent years, numerous studies have highlighted its significant antitumor properties, indicating potential clinical applications and development value. However, the clinical use of cryptotanshinone has been limited due to its poor water solubility and low bioavailability. To overcome these limitations, researchers are exploring new drug delivery systems, and novel formulation systems based on nanotechnology are being developed to improve the delivery and effectiveness of cryptotanshinone. In this review, we aim to consolidate the existing knowledge regarding the antitumor effects of cryptotanshinone and emphasize the latest advancements in its nanoformulation development. We hope to provide insights that will further improve the antitumor efficacy and clinical applicability of cryptotanshinone.
Keywords: bioavailability